Under-reach correction of distance relay in transmission lines - Singh, Ashish Kumar; Joshi, Deepak (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
Conventional distance relaying in transmission line may seriously cause under-reaching or overreaching when receiving side impedance are comparatively greater than sending side impedances and vice versa. These mal-operations become more severe especially in the case that the two networks connected to the ends of the protected lines have extraordinary different equivalent impedances. The protection zones of ground fault elements of distance relay can be modified adaptively in a quadratic function form with the present magnitude and power factor of load, based upon the user setting values. The behavior of a distance relay on a single circuit transmission line and double circuit transmission line is analyzed and simulated using EMTDC/PSCAD software. Transmission lines are modeled by using Bergeron model in PSCAD program for simulation purposes. A new non-iterative algorithm is proposed, which produces a secure decision to trip only the faulted phases during single line to ground fault, for under-reach correction in basic distance relaying scheme. PSCAD/EMTDC software is used to generate time series of phase current following a line to ground fault in the single and twin circuit parallel line model and is captured in COMTRADE file. This file serves as an input to the MATLAB based code of the proposed non-iterative algorithm.